2014
DOI: 10.1093/mnras/stu545
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy cluster mass reconstruction project – I. Methods and first results on galaxy-based techniques

Abstract: This paper is the first in a series in which we perform an extensive comparison of various galaxy-based cluster mass estimation techniques that utilise the positions, velocities and colours of galaxies. Our primary aim is to test the performance of these cluster mass estimation techniques on a diverse set of models that will increase in complexity. We begin by providing participating methods with data from a simple model that delivers idealised clusters, enabling us to quantify the underlying scatter intrinsic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 101 publications
6
60
0
Order By: Relevance
“…This is analogous to what is found by most group mass estimation methods when the group center and its velocity are provided (see Old et al 2014, although Old et al 2015 find that a Bayesian fitted slope of the estimated versus true mass relation is typically unity). Figure 15 shows that MAGGIE and Yang do not underestimate the EG masses of primary fragments as frequently as does the FoF algorithm.…”
Section: Mass Accuracysupporting
confidence: 72%
“…This is analogous to what is found by most group mass estimation methods when the group center and its velocity are provided (see Old et al 2014, although Old et al 2015 find that a Bayesian fitted slope of the estimated versus true mass relation is typically unity). Figure 15 shows that MAGGIE and Yang do not underestimate the EG masses of primary fragments as frequently as does the FoF algorithm.…”
Section: Mass Accuracysupporting
confidence: 72%
“…The applied FoF group construction method has been tested on mock galaxy surveys in Nurmi et al (2013) and Old et al (2014). Both papers indicate that the used FoF parameters (LL in radial and transversal direction) provide statistically reliable groups.…”
Section: Flux-limited Galaxy Groups/clustersmentioning
confidence: 99%
“…This increase of the mean distance is an expected effect of a fluxlimited survey. A similar LL determination method was used by Old et al (2014), where various group-finding algorithms (including the one presented here) are compared. Old et al (2014) showed that the groups extracted using such LL strategy are statistically correct and the corresponding group properties are meaningful.…”
Section: Flux-limited Galaxy Groups/clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar procedure to calculate the dynamical mass of the supercluster was used in Einasto et al (2015). The reliability of group mass estimation method and mass errors were analysed in Old et al (2014Old et al ( , 2015, where various mass estimation methods were tested on mock galaxy catalogues. The method used in this work performs reasonably well without a clear bias between true and estimated masses.…”
Section: Masses Of Superclustersmentioning
confidence: 99%